Building a Culture of Literacy in Schools: The Role of Students in Improving the Quality of Elementary School Education - Furbani, Widiastuti (MSJ : Majority Science Journal, 2024)
Literacy culture in schools plays a crucial role in improving the quality of education. Through strengthening the role of students, literacy becomes a strategic instrument to develop critical, creative and collaborative skills. This article reviews how students can be the main actors in creating a strong literacy culture through various innovative programs, such as reading and writing activities that actively involve them. In addition, collaboration between students, teachers and parents is also very important to create a conducive literacy environment. This study used a qualitative approach with data collection techniques in the form of observation, interviews and literature study. The results showed that direct student involvement in literacy activities has a significant positive impact on the success of literacy culture in schools. Students who are actively involved in reading and writing activities not only develop their literacy skills but also improve their critical and creative thinking skills. Thus, a thriving literacy culture in schools not only improves the quality of education but also shapes the character of students who are more independent and collaborative.